Designing Compound Exercises According to FT4A Computer Program And Their Effect on Developing Passing In Youth Soccer Players Aged 17 – 18 Years Old - Mohammed, Saher (Journal of Physical Education, 2017)
The problem of the research lies in designing exercises using computer program FT4A to develop the process of understanding and comprehending passing in soccer. The aim of the research was to design compound exercises using computer program FT4A and identifying the effect of these exercises on the development of passing n youth soccer players aged 17 – 18 years old. The researcher used the experimental method. The subjects were (24) soccer players from Al Shorta and Al Zoraa clubs divided into two groups. The researcher concluded that the first experimental group was better than the second in the development of passing after using FT4A. Finally he concluded that the compound exercises designed by FT4A computer program was better that exercises not designed by this program